2023
DOI: 10.31234/osf.io/w6x54
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Motor learning without physical practice: The effects of combined action observation and motor imagery practice on cup-stacking speed

Abstract: In this study we explored training effects for combined action observation and motor imagery (AO+MI) instructions on a complex cup-stacking task, without physical practice. Using a Graeco-Latin Square design, we randomly assigned twenty-six participants into four groups. This counterbalanced the within-participant factor of practice condition (AO+MI, AO, MI, Control) across four cup-stacking tasks, which varied in their complexity. On each of the three consecutive practice days participants experienced twenty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…At baseline, post and retention test time points the direction of significant differences between tasks replicated the findings of Binks et al (77). The mean times for each cup-stacking task (i.e., Greek letters within the design) were significantly different from one another, which identified increasing complexity across the four tasks in the following order: 1-10-1 > 6-6 > 3-6-3 > 3-3-3-3.…”
Section: Accounting For Extraneous Variables In the Research Designsupporting
confidence: 82%
See 2 more Smart Citations
“…At baseline, post and retention test time points the direction of significant differences between tasks replicated the findings of Binks et al (77). The mean times for each cup-stacking task (i.e., Greek letters within the design) were significantly different from one another, which identified increasing complexity across the four tasks in the following order: 1-10-1 > 6-6 > 3-6-3 > 3-3-3-3.…”
Section: Accounting For Extraneous Variables In the Research Designsupporting
confidence: 82%
“…This result is in line with previous betweengroup studies demonstrating beneficial practice effects for AO + MI training in neurotypical populations compared to AO [e.g., (118)], or MI [e.g., (71,72)], or compared to both AO and MI (74-76). Building upon the significant findings of Binks et al (77), the present study is the first to fully counterbalance the research design to control for several common sources of extraneous variability, while analyzing motor learning via mental practice in a stroke survivor population.…”
Section: Action Observation During Motor Imagery E Ectsmentioning
confidence: 98%
See 1 more Smart Citation
“…Binks et al [6] delved deeper into motor learning intricacies, investigating the training effects of AO + MI instructions on a complex cup-stacking task. Their study suggested that even complex motor skills, traditionally relying heavily on physical practice, can witness significant enhancements through cognitive interventions like AO + MI.…”
Section: Action Observation and Motor Imagery In Sports And Skill Lea...mentioning
confidence: 99%
“…Numerous studies are showing the motor learning benefits associated with AOMI, even when the actions are beyond the learner's motor repertoire (Aoyama et al, 2020; Binks, Emerson, et al, 2023; Binks, Wilson, et al, 2023; Eaves et al, 2022; Kawasaki et al, 2018; Scott et al, 2023). However, individual AOMI with respect to less experienced and more challenging actions fail to elicit an increase in corticospinal excitability (Eaves et al, 2016; Fourkas et al, 2006; Mizuguchi & Kanosue, 2017), which may be due to less vividness (Moriuchi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%